Coseismic displacement of the 5 April 2017 Mashhad earthquake (Mw 6.1) in NE Iran through Sentinel-1A TOPS data: New implications for the strain partitioning in the southern Binalud Mountains. (January 2019) - Su, Zhe; Yang, Ying-Hui; Li, Yong-Sheng; Xu, Xi-Wei; Zhang, Jingfa; Zhou, Xin; Ren, Jun-Jie; Wang, Er-Chie; Hu, Jyr-Ching; Zhang, Shi-Min; Talebian, Morteza
Highlights: Quantifying the strike- and dip-slip subcomponents of the Mashhad earthquake. Assessment for the future seismic hazard for the Mashhad regions. Provide a new tectonic implications for the strain partitioning dynamics of NE Iran. Abstract: The outward expansion of the northeastern Iranian Plateau is mainly accommodated by a series of widely distributed range-normal thrust and range-parallel strike-slip faults. However, the role of the strike-slip faults in this region's strain-partitioning kinematics remains unclear. The occurrence of the 5 April 2017 Mw 6.1 Mashhad earthquake provides us a rare opportunity to study this topic because this earthquake struck the southern Binalud Mountains, which are experiencing an oblique convergence between the northward-moving Lut Block and the NW-striking Binalud and Kopeh Dagh mountain ranges. We process two paired ascending and descending Sentinel-1A radar-image observations to determine the relative contributions from the dip and strike-dip subcomponents in such an oblique collisional domain. The interferograms along the line-of-sight direction and their converted horizontal and vertical displacements indicate that a thrust with a right-lateral strike-slip fault controlled the rupture process of the Mashhad earthquake, with the maximum dextral shearing and vertical displacements reaching 19.5 cm and 14 cm, respectively. Coseismic surface deformation measurements are also used to estimate the fault geometry and invert the slip distribution along the underlying seismogenic fault. Our best-fit faulting model suggests that the coseismic rupture occurred on a fault plane with a dip angle of 37.5° and strike angle of 324°. The strike-slip subcomponent was more significant than the dip-slip, approaching ∼95 cm, and the dip-slip varied from 10 cm to 47 cm. The seismic-moment release of our preferred fault model is 1.71 × 10 18 Nm, equivalent to a Mw 6.16 earthquake event. We also use the preferred fault model to calculate the Coulomb failure stress (CFS) change at the nearby receiver faults. Combined with an analysis of historical earthquakes and the consistent dextral river deflections along the strike-slip fault systems of the southern Binalud and Kopeh Dagh Mountains, we speculate that the seismogenic structure that triggered the Mashhad earthquake should have been one strand fault of the NW–SE-striking Kashafrud fault system. The strike-slip faults in NE Iran play an important role in accommodating the lateral transport of crustal material from the convergence front of the Lut Block and Binalud fragments and providing commonly distributed anticlockwise rotation around a vertical axis.